Legal Framework and Issues in Hazardous Waste Management: Kerangka Hukum dan Permasalahan Pengelolaan Limbah B3 - Setiadi, Fajar Nur; Rosnawati, Emy (Universitas Muhammadiyah Sidoarjo, 2024)
Background: Environmental protection is crucial for preventing pollution and maintaining balance. Specific background: Hazardous waste (B3) significantly contributes to pollution, especially when mismanaged. Knowledge gap: Despite existing laws like Law No. 32/2009 on Environmental Protection, enforcement remains a challenge. Aims: This study analyzes B3 waste management under Indonesian regulations and assesses local programs and infrastructure developments. Results: While regulations and programs are in place, such as B3 handling policies and a new waste processing plant, poor compliance hampers effectiveness. Novelty: The study highlights evolving local strategies for improving B3 management. Implications: Stronger enforcement and integrated solutions are key to reducing environmental risks and achieving sustainability. Highlights : Local strategies are evolving to improve B3 waste management. Compliance with environmental regulations remains a significant issue. Technological solutions like waste incineration offer promising improvements. Keywords: Environmental protection, hazardous waste, B3 management, regulatory enforcement, sustainability